Department and product in Bank Rakyat Seremban / Muhammad Redzuan Shah Mazlan - Shah Mazlan, Muhammad Redzuan (Faculty of Business and Management, 2011)
Finance Industrial Training is the program introduced by Faculty of Business Management, UiTM to all undergraduate Finance students as partial requirement for them to acquire a Bachelor of Degree in Finance. It is proud to mention that I have finished my internship in Bank Kerjasama Rakyat Malaysia at Seremban Negeri Sembilan, BKRM successfully for 5 months. In addition, as one of the Islamic Banking in Malaysia, BKRM’s services are very wide. Some of the services that BKRM used will be discussed in this report. Throughout this report, I will also emphasize on what activities that I have conducted in several departments that I have attached. During the training, I have experienced new things and faced real working environment. Apart from that, I have learnt many theoretical parts in Islamic Banking field. At the same time, I was able to relate what I have learnt in university with all lessons in BKRM. Here, I would like to recommend some suggestion to respected parties in order to perform better in future.